SOLUTION OF PALEO-HYDROGEOLOGICAL PROBLEMS BY ELECTRICAL VES METHOD: (case study the Lake Sevan catchment basin) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In this scientific article, besides our research, a number of research and production enterprises in the Republic of Armenia, as well as materials of hydrogeological and geophysical studies have been used for various types of exploration of the Lake Sevan catchment basin. For this purpose, we have used electrical, basically vertical electrical sounding (VES) field data as a control method and materials to drill wells cuts the measured points. According to electro-sounding materials, we have investigated the strength of the waterproof layer of the area and, taking into account the absolute altitudes of the measured points, according to local watersheds, we have identified the regions of the corresponding direction, which we called the map of the paleo-hydro-zoning of the the Lake Sevan catchment basin.
Keywords: water catchment basin; electro-sounding; well; groundwater flow; paleo-relief; modern watershed; old (buried) watershed; balance; hydrogeological area; waterproof layer